Теоретичний базис формування системи адаптації промислового підприємства до умов мінливого конкурентного середовища - Сікєтіна, Наталія Геннадіївна (My University, 2020)
Стаття присвячена актуальним питанням адаптації промислових підприємств під впливом мінливого конкурентного середовища. Досліджено теоретичні питання економічної категорії «адаптація», «зовнішнє середовище» та «система адаптації» відносно промислових підприємств. Визначено класифікацію факторів зовнішнього середовища на основі аналізу літературних джерел. Розглянуто структуру адаптації систем та виділено її два основні види – параметричну та структурну адаптацію. Визначено теоретичний базис вивчення процесу формування системи адаптації промислового підприємства. Теоретичний базис представлено у вигляді взаємозалежної сукупності базових категорій – система, формування, адаптація, середовище, підприємство. Адаптацію промислового підприємства визначено як здатність підприємства генерувати певний рівень чистого доходу й конкурентоспроможності продукції при входженні у мережеву структуру на тривалій основі, займає верхній рівень ієрархії адаптаційних ознак підприємства у мінливому конкурентному середовищі.

An industrial enterprise is such a market economy entity that, depending on the state of material production, NTP and service, provides a certain level of social production and wealth in the country. At the same time, in the process of its interaction with the changing external, and consequently, the internal environment, the functioning of the enterprise is at risk of its impact. A characteristic feature of the current stage of development of the world economy is its high dynamism and high speed of the process of formation of market relations. Therefore, a considerable number of domestic industrial enterprises, in the face of the financial crisis, have shown their unwillingness to respond to such changes and confidently adapt to them in the external and internal environment. In recent years, the content of competition has changed and is winning over an entity whose knowledge enables it to create competitive advantages, that is, to identify the potential of any value, to generate unique ideas and knowledge that may interest future consumers of its products. Effective solutions to such problems contribute to the growth of the national economy and increase in its investment attractiveness as well. The main objective of the article is to substantiation of the theoretical basis for the formation of an enterprise adaptation system to the conditions of dynamic competitive environment. The specific socio-economic reality of domestic industrial enterprises is variable, diverse and complex. These properties of economic reality are the main causes of the difficulties of its scientific knowledge. The extremely changing nature of the market environment distorts market conditions, when traditional methods of conducting economic activity no longer guarantee the maintenance of the acquired market positions. The process of forming market relations in Ukraine has its own characteristics and characterized by a high degree of asymmetry regarding the potential of production of competitive products. It may induce individual industrial enterprises to make it impossible to produce competitive products. Theoretical basis for the study of the process of forming the adaptation system of an industrial enterprise presented in the form of an interdependent set of basic categories: adaptation, basis, system, enterprise, environment, and opportunities, potential. The proposed definitions can used to create a system for adapting the structure of an industrial enterprise in a changing competitive environment.
Formation the theoretical basis of the industrial enterprise adaptation system to the changes of the competitive environment
Keywords: управління підприємством; організаційно-економічна система; конкурентоспроможність; зовнішнє середовище; інноваційний потенціал; adaptation; enterprises; environment; opportunities